Альфвенiвський нагрiв плазми в стелараторi Ураган-2М - Moiseenko, V. E.; Lozin, A. V.; Kozulia, M. M.; Mironov, Yu. K.; Romanov, V. S.; Konovalov, V. G.; Shapoval, A. N. (Publishing house "Academperiodika", 2018)
A new antenna of the crankshaft type is successfully employed in experiments on Uragan-2M. It creates and heats plasma at frequencies below the ion-cyclotron frequency. The discharge created with the antenna is “hot” during few milliseconds and then fades under strong impurity influx into plasma. The radial profiles of OV and CV optical emissions are investigated. Both are concave, especially the OV profile. This can be explained by some burnout of O4+ andC4+ ions and its transition to O5+ and C5+ ionization states near the magnetic axis. The magnetic field optimisation and the Alfv´en heating allowed burning-out the light impurities prior to the discharge degradation. The experiments in support of the fusion-fission stellarator reactor concept are also carried out. The stellarator-mirror machine is modeled by switching off a toroidal field coil at Uragan-2M. The embedded mirror with lower magnetic field is created in this way. Plasma is successfully produced and heated in such a combined magnetic trap.